2015
DOI: 10.1097/rlu.0000000000000641
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Comparison of 18F-FDG and 68Ga-DOTA-Peptide PET/CT for Pulmonary Carcinoid

Abstract: Overall diagnostic performance of PET/CT in detecting PC is optimal when integrating 18F-FDG and 68Ga-DOTA-peptide PET/CT findings. In the subgroup analysis, the SUV max ratio seems to be the most accurate index in predicting TC. Both methods should be performed when PC is suspected or when the histological subtype is undefined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 25 publications
1
47
0
3
Order By: Relevance
“…However, many authors now see SRI and FDG not as competitors but as complementary diagnostic tools 24-28. For example, Nilica and colleagues used dual-tracer imaging in the setting of PRRT in 66 patients with metastatic NET.…”
Section: Are Results Of Sri-pet and Fdg-pet Complementary?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, many authors now see SRI and FDG not as competitors but as complementary diagnostic tools 24-28. For example, Nilica and colleagues used dual-tracer imaging in the setting of PRRT in 66 patients with metastatic NET.…”
Section: Are Results Of Sri-pet and Fdg-pet Complementary?mentioning
confidence: 99%
“…Some teams are investigating dual-tracer imaging for preoperative prognostication and risk stratification in pancreatic tumors or pulmonary carcinoid 27,28. Lococo et al showed that a ratio of ≥1.19 between the SUVmax on SRI-PET and the SUVmax on FDG-PET can differentiate between a typical or atypical carcinoid 28. Preoperative biopsy has difficulty in distinguishing between these entities 29.…”
Section: Are Results Of Sri-pet and Fdg-pet Complementary?mentioning
confidence: 99%
“…(23) and Srirajaskanthan et al (28), who provide direct comparison to 111 In-pentetreotide imaging. Recently Has Simsek et al (29) and Lococo et al (30) reported the complementary roles of 68 Ga-DOTATATE and 18 F-FDG PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…The small size of NETs makes it difficult for conventional anatomic imaging to visualize the primary tumor or its metastases, given that these modalities are unable to depict specific endocrine features; consequently, the diagnostic accuracy of functional imaging is significantly higher than that of conventional imaging (7,(11)(12)(13)(14). 18 F-FDG PET/CT imaging has also been compared with 68 Ga-DOTA peptide imaging in several studies, which have shown it to have variable sensitivity in detecting NETs (15)(16)(17)(18)(19)(20)(21)(22). However, the presence of increased glucose in NETs highlights an increased propensity for invasion and metastasis, and 18 F-FDG PET/CT accordingly has higher sensitivity in delineating disease extent, especially in aggressive and high-grade tumors (23).…”
Section: Discussionmentioning
confidence: 99%